Bronchoalveolar Lavage Fluid-Derived Exosomes: A Novel Role Contributing to Lung Cancer Growth - Yang, Yibao; Ji, Ping; Wang, Xuan; Zhou, Hao; Wu, Junlu; Quan, Wenqing; Shang, Anquan; Sun, Junjun; Gu, Chenzheng; Firrman, Jenni; Xiao, Weidong; Sun, Zujun; et al. (Frontiers in Oncology, 2019)
Exosomes are nanovesicles produced by a number of different cell types and regarded as important mediators of cell-to-cell communication. Although bronchoalveolar lavage fluid (BALF) has been shown to be involved in the development of tumors, its role in lung cancer (LC) remains unclear. In this article, we systemically studied BALF-derived exosomes in LC. C57BL/6 mice were injected with Lewis lung carcinoma cells and exposed to non-typeable Haemophilus influenza (NTHi) lysate. The analysis showed that the growth of lung tumors in these mice was significantly enhanced compared with the control cohort (only exposure to air). Characterization of the exosomes derived from mouse BALF demonstrated elevated levels of tumor necrosis factor alpha and interleukin-6 in mice exposed to NTHi lysates. Furthermore, abnormal BALF-derived exosomes facilitated the development of LC in vitro and in vivo. The internalization of the BALF-derived exosomes contributed to the development of LC tumors. Collectively, our data demonstrated that exosomes in BALF are a key factor involved in the growth and progression of lung cancer.